Problem of Unification Hijri Calendar - Wahidin, Nurul Wasilah (Universitas Islam Negeri Mataram, 2022)
The presence of an accurate, consistent, and unified calendar system is a strength in civilization. Nevertheless, an easy thing to do through a long history. Globally the calendar used is still the Gregorian calendar around the world which is based on the revolution of the sun. In the Islamic world, the Hijri calendar is also known based on the calculation of the moon's revolution against the earth. the existence of the hijri calendar as a time marker for Muslims in worship and muamalah. However, entering the 14th century hijriyah, the hijri calendar system cannot be used uniformly in the Islamic world. This has become a major concern for Islamic countries, including Indonesia, to formulate efforts to unify the hijriyah calendar, but until now, through several collaborations and conferences, Islamic countries have not been successful due to several factors, both fiqh and astronomical.